2020
DOI: 10.1016/j.psj.2020.09.082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of chlorogenic acid in reducing small intestine injury, oxidative stress, and inflammation in chickens challenged with Clostridium perfringens type A

Abstract: The goal of the study was testing the effects of chlorogenic acid ( CA ) supplementation on small intestine healthiness, growth performance, oxidative stress, inflammatory response, and blood biochemical indices in specific-pathogen-free (SPF) chickens after infection with Clostridium perfringens (CP) type A. In this study, 324 1-day-old male SPF chickens were randomly distributed into 6 groups: control group; CA group; CP infection group; CA + CP group; antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 50 publications
4
36
0
Order By: Relevance
“…Previous studies [ 26 , 42 ] reported that C. perfringens challenge reduced body weight gain and feed intake, while heighten FCR of broilers, which were similar to our results. The supplementation of plant extracts, including tannin and polyphenol compounds, have been proved to be effective against NE [ 46 , 66 ], but the effect of EA on the growth performance of broilers has not been reported. In this study, the addition of EA in diet increased ADG and decreased FCR of broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 26 , 42 ] reported that C. perfringens challenge reduced body weight gain and feed intake, while heighten FCR of broilers, which were similar to our results. The supplementation of plant extracts, including tannin and polyphenol compounds, have been proved to be effective against NE [ 46 , 66 ], but the effect of EA on the growth performance of broilers has not been reported. In this study, the addition of EA in diet increased ADG and decreased FCR of broilers.…”
Section: Discussionmentioning
confidence: 99%
“…The small intestine is an important place for digestion and absorption of the animal body, so the morphological structure of the small intestine is often used as an indicator to measure the digestion and absorption functions of an animal. The length of the villi and the depth of crypts reflect the effective area and function of intestinal digestion and absorption of nutrients, and their ratio comprehensively reflects the functional status of the small intestine ( 49 ): the larger the ratio, the larger the contact area of the intestinal mucosa with nutrients and the stronger digestion and absorption functions. In this study, we showed that dietary antimicrobial peptide plectasin (200 mg plectasin/kg of diet) could increase the ratio between the villus length and crypt depth of the ileum, jejunum, and duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…We began to feed baicalin to the corresponding groups at the age of 1 day. The composition and nutritional level of basal feeding were shown in Table 2 [ 21 ]. The chickens in the H9N2 AIV infection group and H9N2 AIV infection plus feeding baicalin group were infected with H9N2 AIV at the age of 9 days, and the infection dose was 3-fold 10 6 EID 50 /0.1 mL.…”
Section: Methodsmentioning
confidence: 99%